2019
DOI: 10.1007/s10899-019-09908-2
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy of a Gambling Prevention Program Among High-School Students

Abstract: Youth problem gambling has become an emergent public health issue, and adolescents constitute a vulnerable age group for the development of gambling-related problems. Although there is research concerning the risk factors of youth problem gambling, rigorous evaluations of the effectiveness of preventive initiatives is still rare. The present study evaluated the efficacy of an integrative intervention to prevent youth problem gambling based on a multidimensional set of factors including gambling-related knowled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
32
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 51 publications
1
32
0
1
Order By: Relevance
“…Moreover, recent studies have demonstrated that prevention programs focused on cognitive distortions (and delivered in school settings) are effective in reducing misconceptions about gambling and the time spent in gambling activities. These studies also demonstrated the stability of the training effects over time and their potential to offset the trajectory toward disorder (Calado et al 2020 ; Donati et al 2018 ).…”
Section: Discussionmentioning
confidence: 95%
“…Moreover, recent studies have demonstrated that prevention programs focused on cognitive distortions (and delivered in school settings) are effective in reducing misconceptions about gambling and the time spent in gambling activities. These studies also demonstrated the stability of the training effects over time and their potential to offset the trajectory toward disorder (Calado et al 2020 ; Donati et al 2018 ).…”
Section: Discussionmentioning
confidence: 95%
“…In addition, online players have a higher rate of problematic gambling than offline players [ 13 ] and bet on more modes of play [ 14 , 15 ]. In adolescence, critical thinking and other cognitive skills are still developing, which makes adolescents more prone to gambling [ 4 , 16 , 17 , 18 , 19 , 20 ]. In this sense, the prevalence of risk and/or problem gambling among adolescents is higher than in adults [ 4 , 17 , 18 , 19 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…The latter include components to reduce gambling misinformation, probability, cognitive bias about gambling, and risk perception. For the skills training, a wide variety of topics are included, such as self-esteem, social and coping skills, decision-making, problem solving and skills to refuse to gamble [ 16 , 28 , 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…In Spain, the most prominent programs are ADITEC [ 34 ], which is focused on abuse of new technologies, and “¿Qué Te Juegas?”, which addresses gambling disorders [ 35 ]. Of note at the international level are PROTECT, for problematic Internet use [ 36 ], and the gambling prevention program [ 37 ]. Currently, there are no programs to prevent Internet gaming disorders in Spain.…”
Section: Introductionmentioning
confidence: 99%
“…", which addresses gambling disorders [35]. Of note at the international level are PROTECT, for problematic Internet use [36], and the gambling prevention program [37]. Currently, there are no programs to prevent Internet gaming disorders in Spain.…”
Section: Introductionmentioning
confidence: 99%